Hubungan Personal Hygiene dengan Kejadian Keputihan pada Remaja Putri : Relationship between Personal Hygiene and the Incidence of Vaginal Discharge in Adolescent Female - Siallagan, Dorsinta; Marlinda; Hanny Desmiati; Reni Nofita; Nuntarsih; Chirunnisa Minarni Alamsyah; Mardi Yana (Universitas Ngudi waluyo, 2025)
Vaginal discharge is a reproductive health problem that is often experienced by adolescent girls and its incidence increases every year. Vaginal discharge is the discharge of fluid other than blood from the vagina which can be pathological or physiological which is influenced by hormones and infections such as fungi, parasites and pathology. If the pathology is not treated, vaginal discharge can affect infertility in fertile women (WUS). In 2021, there were 70% of cases of vaginal discharge. Lack of understanding and poor personal hygiene practices can be triggers for vaginal discharge. This study aims to determine the incidence of vaginal discharge based on personal hygiene behavior in adolescent girls. The research method in this study uses descriptive analytic with a cross-sectional approach. The location of the study was carried out at 12 integrated service post in Suradita Village, Tangerang Regency. The population in this study was 168 adolescent female respondents who experienced vaginal discharge, while the sample in this study after being selected based on inclusion and exclusion criteria was 130 adolescent female respondents. The instrument used in the study was a self-awareness survey questionnaire (SMD). The results showed that 19.2% experienced pathological vaginal discharge and 16.2% of female adolescents had poor personal hygiene. Bivariate analysis showed a significant relationship between personal hygiene behavior and the incidence of vaginal discharge in female adolescents with a p-value of 0.001 (p <0.05). Education on good personal hygiene is needed to increase adolescents' knowledge on how to prevent and overcome vaginal discharge so that pathological vaginal discharge in adolescents can be suppressed. Abstrak Keputihan merupakan masalah kesehatan reproduksi yang sering dialami oleh remaja putri dan kejadiannya meningkat setiap tahunnya. Keputihan adalah keluarnya cairan selain darah dari liang vagina dapat bersifat patologis maupun fisiologis yang dipengaruhi oleh hormonal dan infeksi seperti jamur, parasit serta patologis. Apabila tidak ditanggulangi keputihan patologis dapat mempengaruhi infertilitas pada wanita subur (WUS). Tahun 2021, terdapat 70% kasus keputihan. Kurangnya pemahaman dan praktik personal hygiene yang buruk dapat menjadi faktor pemicu kejadian keputihan. Penelitian ini bertujuan untuk mengetahui kejadian keputihan berdasarkan perilaku personal hygiene pada remaja putri. Metode penelitian dalam penelitian ini menggunakan deskriptif analitik dengan pendekatan cross-sectional. Lokasi penelitian dilaksanakan pada 12 Posyandu yang terdapat di Desa Suradita Kabupaten Tangerang. Populasi dalam penelitian ini adalah 168 responden remaja putri yang mengalami keputihan, sedangkan sampel dalam penelitian ini setelah di lakukan pemilihan berdasarkan kriteria inklusi dan ekslusi sebanyak 130 responden remaja puteri. Intrument yang digunakan dalam penelitian adalah kuesioner survey mawas diri (SMD). Hasil penelitian menunjukkan 19,2 % mengalami keputihan patologis dan 16,2% personal hygiene remaja putri buruk. Analisis bivariat menunjukkan adanya hubungan yang signifikan antara perilaku personal hygiene dengan kejadian keputihan pada remaja putri dengan nilai p-value 0,001 (p < 0,05). Diperlukan edukasi mengenai personal hygiene yang baik untuk menambah pengetahuan remaja cara mencegah dan mengatasi keputihan sehingga keputihan patologis pada remaja dapat ditekan.